Use of fibular graft in Masquelet technique in osteomyelitis of long bones-a novel modification in the technique - Kharat, Aniket; Aher , Deepak (International Journal of Research in Orthopaedics, 2023)
Background: Improper treatment of acute osteomyelitis mostly leads to chronic osteomyelitis. In the year 2000, Alain C. Masquelet described the Induced membrane technique for the first time. In this study, we aimed to determine the clinical efficiency of the Masquelet technique for bone loss due to osteomyelitis in the long bones. Methods: This study was conducted at our tertiary care centre Shri Vasantrao Naik medical college and hospital, Yavatmal between August 2016 and September 2020. Masquelet technique with some modification was performed in all cases. Results: In first stage, the defects were filled with antibiotic-loaded polymethyl methacrylate (PMMA) cement after radical debridement. In second stage after 6 to 8 weeks we used a combination of fibular strut graft with iliac cancellous graft. X-rays were taken before second stage and after 3 months, 6 months and 1 year to see for the union. The study included 10 patients, with 6 males and 4 females with mean age of 34 years (20 to 54). The mean duration of bone infection was 4 months (range: 3-5 months). All patients had an average follow-up period of 16 months (range, 12-24 months). Radiographic evidence of bone union was seen in 6 months (3 to 9 months) infection was not seen in any case. Conclusions: This modified Masquelet is an effective method for the treatment of chronic osteomyelitis of the long bones.